Wages and the bargaining regime under multi-level bargaining: Belgium, Denmark and Spain - Robert Plasman; Michael Rusinek; François Rycx (Institute for the Study of Labor (IZA), 2006)
Using a unique harmonized matched employer-employee dataset (European Structure of Earnings Survey, 1995), we study the impact of the regime of collective bargaining on wages in the manufacturing sector of three countries that are characterized by a multi-level system of bargaining: Belgium, Denmark and Spain. Our findings show that, compared to multi-employer bargaining, single-employer bargaining has a positive effect both on wage levels and on wage dispersion in Belgium and in Denmark. In Spain, single-employer bargaining also increases wage levels but reduces wage dispersion. Our interpretation is that in Belgium and Denmark, single-employer bargaining is used to adapt pay to the specific needs of the firm while, in Spain, it is mainly used by trade unions in order to compress the wage distribution.
Keywords: J31; J51; J52; 330; collective bargaining; wage structure; Tarifpolitik; Lohnstruktur; Belgien; Dänemark; Spanien